Large Mammals - Mohd-Azlan, J.; Andrew Alek, Tuen; Simon, Alfanso Mckenzie; Engkamat Lading, Gilbert; Dayang Nuriza, Mustafa Abdul Rahman (Natural History Publication and in association with Universiti Malaysia Sarawak, 2015)
Mohd-Azlan, J., Andrew Alek Tuen, Alfanso Mckenzie Simon, Gilbert, Engkamat Lading, Dayang Nuriza, Mustafa Abdul Rahman